PERANCANGAN PROMOSI RANDANG ONE SUNGAI PUA DALAM MEDIA BROSUR - HABBY ZAKKY, Dra. Zubaidah, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The design of this brochure describes the information products and ser-vices Randang One Sungai Pua, excellent products from Randang One sungai Pua include Randang Dagiang, Randang Rabu (Paru), Randang Dendeng and Randang Suir (Randang the meat in smooth flat), as well as some catering cuisine services , akikah cuisine and traditional cuisine. The purpose of this promotional brochure design is to provide information about products and services, to be bet-ter known to the public and tourists. The method used in data gathering is by con-ducting interviews, observation, documentation, and literature study. While the method used to analyse data is SWOT analysis method (Strenght, Weakness, Op-portunity, and Threat). To strengthen the design of the brochures are designed various media as a supporting medium of poster, x-banner, shirts, totebag, key-chains, stickers, social media (Instagram), and social media Gojek (Gofood).Keywords : Brosur, Promotion, Randang One, Sungai Pua.